Unexpected rare metastases of renal cell carcinoma - Khoo, Alex; Cheong, Yew (World Journal of Nuclear Medicine, 2020)
Renal cell carcinomas (RCCs) commonly metastasize to the lungs and bones and rarely to the parathyroid, maxillary sinus, and adrenals. It is indeed very rare to have these all these metastases occurring simultaneously in an individual. We share a case of 67-year-old woman provisionally treated for parathyroid carcinoma but subsequently found to actually have metastatic RCC to the left maxillary sinus, parathyroid, lungs, and adrenals on 18F-fluorodeoxyglucose positron emission tomography–computed tomography.
Keywords: 18F-fluorodeoxyglucose; maxillary sinus; metastatic; parathyroid; positron emission tomography–computed tomography; renal cell carcinoma